2007
DOI: 10.1002/micr.20400
|View full text |Cite
|
Sign up to set email alerts
|

Management and functional outcomes of combined injuries of flexor tendons, nerves, and vessels at the wrist

Abstract: A retrospective review of 42 patients with spaghetti wrist lacerations operated on by the author between June 1997 and May 2005 was completed. A total of 31 males and 11 females, average age of 17.1 years (range, 2-40 years), sustained spaghetti wrist injuries. The most frequent mechanisms of injury were accidental glass lacerations (55%), knife wounds (24%), and electrical saw injuries (11%). An average of 9.16 structures was injured, including 6.95 tendons, 1.4 nerves, and 0.8 arteries. The most frequently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 15 publications
3
49
1
4
Order By: Relevance
“…Common patterns of injury include the "ulnar triad," with injury to the ulnar nerve, ulnar artery, and flexor carpi ulnaris, occurring in 31% to 42% of patients. [1][2][3] Similarly, the radial triad injury, with injury to the median nerve, palmaris longus, and flexor carpi radialis, is reported in 23% to 43% of patients. Studies vary in whether injury to the median nerve or ulnar nerve is more common, and simultaneous injury to both median and ulnar nerve ranges from 20% to 48%.…”
mentioning
confidence: 97%
“…Common patterns of injury include the "ulnar triad," with injury to the ulnar nerve, ulnar artery, and flexor carpi ulnaris, occurring in 31% to 42% of patients. [1][2][3] Similarly, the radial triad injury, with injury to the median nerve, palmaris longus, and flexor carpi radialis, is reported in 23% to 43% of patients. Studies vary in whether injury to the median nerve or ulnar nerve is more common, and simultaneous injury to both median and ulnar nerve ranges from 20% to 48%.…”
mentioning
confidence: 97%
“…We assessed sensory recovery in 3 groups according to static 2-point discrimination: less than 10 mm (16 patients, 61%), greater than 10 mm (8 patients, 30%), and totally insensate (2 patients, 9%). 14 Finger range of motion was excellent in 18 fingers ( Fig. 2A, B), good in 7 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Noamann in his own series reported that following combined cuts, 6.5% patients showed a major deformity,13.5% patients showed a minor deformity, and 80% showed no signs of deformity. [15] Hudson reported observing 7 claw deformities throughout the 49 months of follow-up in his 15 combined cut series. [16] Only two patients developed claw hand deformity in our series including 26 patients.…”
Section: Discussionmentioning
confidence: 99%